In vitro and in silico Acetylcholinesterase Inhibitory Activity of Premna serratifolia Linn. - Marimuthu, Srinivasan; Nalban, Nasiruddin; Kumar, Anurag; Prasad, Goli Penchala; Gurav, Arun Manohar (Free Radicals and Antioxidants)
Background: Premna serratifolia Linn. (PS) was studied for phytochemical properties and antioxidant activity, as well as for its ability to inhibit the enzyme Acetylcholinesterase (AchE) and dock with PS molecules. Materials and Methods: An LC-MS/MS and GC-MS analysis of dried leaf extracts was performed for phytochemical identification, radical scavenging assays, and enzyme-based AchE inhibitory activity, as well as structurally-based molecular design of AchE inhibitors. Results: PS leaf extract was screened using phytochemical methods such as GC-MS and LC-MS/MS to identify its active constituents. DPPH radical (alcoholic 49.94 µg/mL and hydroalcoholic 49.89 µg/mL) was significantly inhibited by PS extracts at 20 and 40 µg/mL, as were their respective IC50 values. PS-alcoholic and PS-hydro alcoholic leaf extracts inhibited AchE by 49.45 µg/mL and 49.56 µg/mL, respectively. Conclusion: PS inhibits AchE and in vitro radicals scavenges, demonstrating its potential for reversing cholinergic deficits in Alzheimer's patients.
Keywords: Premna serratifolia Linn; Antioxidants; Acetylcholinesterase; Phytochemicals; Molecular docking; GC-MS/LC-MS analysis; Oxidative stress